Analysis of Pedestrian Satisfaction toward the Repurposing of Sidewalks along Muara Karang Raya Street - Yandrie, Fernando Donica; Widyaningsih, Nunung (Universitas Ibn Khaldun Bogor, 2026)
This study aims to analyze the quality of pedestrian pathways along Muara Karang Raya Street both technical and user perception perspectives. The research methodology includes evaluation of existing conditions, measurement of Level of Service (LOS), Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). Findings indicate that while the sidewalks technically perform well with LOS category D, its disturbances from illegal parking, street vendors, and online motorcycle taxis. User satisfaction level reaches 55.95%, indicating moderate satisfaction despite various constraints. IPA analysis reveals that the aspect of orderliness (presence of street vendors/PKL, illegal parking, and online motorcycle taxis) and sidewalk width are in quadrant I; slope, supporting facilities (trash bins, lighting, seating), facilities for disabled persons, and presence of shelters are in quadrant II, accessibility to/from sidewalks, safety, and physical obstacles are in quadrant III, and sidewalk surface conditions are in quadrant IV. The study recommends sidewalk usage regulation, improvement of supporting facilities, and routine maintenance to optimize pedestrian functions. These findings provide significant contributions for pedestrian-oriented public space planning in urban areas.